The Pre-Exposure Prophylaxis Stigma Scale: Measurement Properties of an Adaptation in German and French - Alexander Ort; Tess Bardy (Frontiers Media S.A., 2024)
Objectives:This study aimed to adapt and validate the HIV PrEP Stigma Scale (HPSS) in French and German languages (HPSS-FR/DE) and assess its applicability across diverse linguistic and cultural contexts.Methods:The original scale was adapted to French and German and administered through an online survey in multiple European nations. A four-factor structure was extracted from the data, including negative social consequences, social pressure, self-support, and external support. The scale's construct validity, reliability, and cross-linguistic consistency were evaluated.Results:The adapted HPSS-FR/DE demonstrated robust psychometric properties, good construct validity, acceptable reliability, and consistent measurement across different languages. This adaptation enhances its utility in multicultural settings, offering a comprehensive tool to assess PrEP-related stigma.Conclusion:This study provides a suitable tool to address PrEP stigma in multicultural environments to enhance PrEP uptake and adherence among men who have sex with men. Moreover, it lays the groundwork for further investigations into PrEP stigma across diverse populations and cultural settings, enabling the development of targeted public health interventions and policies to combat this issue effectively.